The Analysis Study of Prevalence, Management and Outcome of Renal Trauma in Pediatrics: A Comprehensive Systematic Review - Kaloka, Rizal Mustaqim; Suselin, Gita Tanbao (International Medical Journal Corp. Ltd, 2024)
Background: Acute kidney injury (AKI) in children is a critical condition influenced by diverse factors, including surgery, critical illness, and nephrotoxin exposure. It affects up to 50% of pediatric ICU admissions and has significant mortality implications, especially post-heart surgery and in the presence of inotropes or ventilation. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Pediatric renal injury, including acute kidney injury (AKI) and its long-term implications, presents a significant clinical challenge across diverse settings. Recent studies highlight varying AKI incidences and outcomes, underscoring the need for effective management strategies and long-term renal surveillance to mitigate mortality and chronic kidney disease risks.